Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732807
|View full text |Cite
|
Sign up to set email alerts
|

Pretty Pelvis

Abstract: Prolonged sitting can be detrimental to our postures which can cause spinal and pelvic problems. It may also lead to a shortened lifespan due to its adverse impact on cardio metabolic health. One way of preventing and mitigating these risks is to break sedentary time. We find it difficult, however, to actively monitor ourselves and commit to making these breaks in the middle of studying or working. The work presented in this paper proposes a motivational smartphone application that connects to a sensor-equippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…These parts of the body have been associated with a lot of repetitive workplace stress injuries based on bad postures (Anderson and Oakman, 2016;Catanzarite et al, 2018;Krajnak, 2018). The study by Min et al (2015) and Mudiyanselage et al (2021) presents closely related concepts. Though these studies explored parts of the body such as the back, spine, arm, and wrists, they used sensors, which might not be comfortable for users of systems.…”
Section: Accessibility Technologies and Healthy Practicesmentioning
confidence: 98%
See 1 more Smart Citation
“…These parts of the body have been associated with a lot of repetitive workplace stress injuries based on bad postures (Anderson and Oakman, 2016;Catanzarite et al, 2018;Krajnak, 2018). The study by Min et al (2015) and Mudiyanselage et al (2021) presents closely related concepts. Though these studies explored parts of the body such as the back, spine, arm, and wrists, they used sensors, which might not be comfortable for users of systems.…”
Section: Accessibility Technologies and Healthy Practicesmentioning
confidence: 98%
“…Research has explored persuasive technologies in relation to best workplace practices. This includes taking regular breaks (Jafarinaimi et al, 2005 ; Ludden and Meekhof, 2016 ; Ren et al, 2019 ), fitness apps (Mohadis et al, 2016 ; Ahtinen et al, 2017 ; Paay et al, 2022 ), feedback systems and wearable devices (Bootsman et al, 2019 ; Jiang et al, 2021 ), workstation movement (Min et al, 2015 ; Damen et al, 2020a , b ), chair, desk, and monitor height adjustments (Kronenberg and Kuflik, 2019 ; Kronenberg et al, 2022 ), posture correction (Min et al, 2015 ; Bootsman et al, 2019 ; Kim M. T. et al, 2019 ), mouse/keyboard use and reduction of glare and reflection (Bailly et al, 2016 ), and other healthy work behaviors (Berque et al, 2011 ; Mateevitsi et al, 2014 ; Gomez-Carmona and Casado-Mansilla, 2017 ; Jiang et al, 2021 ; Brombacher et al, 2023 ; Haliburton et al, 2023 ; Robledo Yamamoto et al, 2023 ).…”
Section: Related Workmentioning
confidence: 99%
“…Persuasive systems based on the Yolo-V3 model can be trained to recognize various environmental conditions, such as the lighting conditions of the room, desk height, and leg position of users. While previous study by Min et al (2015) demonstrated the potential of using sensor reading based on back and arm movements, expanding to recognize more positions would necessitate multimodal datasets, sensors, and strategically positioned cameras to provide users with comprehensive feedback. It is important to note that this approach may require privacy permissions.…”
Section: Discussionmentioning
confidence: 99%
“…Research has explored persuasive technologies in relation to best workplace practices. This includes taking regular breaks (Jafarinaimi et al, 2005;Ludden and Meekhof, 2016;Ren et al, 2019), fitness apps (Mohadis et al, 2016;Ahtinen et al, 2017;Paay et al, 2022), feedback systems and wearable devices (Bootsman et al, 2019;Jiang et al, 2021), workstation movement (Min et al, 2015;Damen et al, 2020a,b), chair, desk, and monitor height adjustments (Kronenberg and Kuflik, 2019;Kronenberg et al, 2022), posture correction (Min et al, 2015;Bootsman et al, 2019;Kim M. T. et al, 2019), mouse/keyboard use and reduction of glare and reflection (Bailly et al, 2016), and other healthy work behaviors (Berque et al, 2011;Mateevitsi et al, 2014;Gomez-Carmona and Casado-Mansilla, 2017;Jiang et al, 2021;Brombacher et al, 2023;Haliburton et al, 2023;Robledo Yamamoto et al, 2023).…”
Section: Persuasive Technologies and The Workplacementioning
confidence: 99%
See 1 more Smart Citation